Research on the delay model of single intersection in the oversaturated state - Fu-yang CHEN; Xiao-yue YAN; Bin JIANG (物联网学报)
The oversaturated state of the intersection is mainly manifested as the queuing vehicles are not completely dissipated at the end of a green light phase.In order to cope with the traffic congestion,the mathematical model of an intersection is built.The relative regularity of arrival rate and departure rate of vehicles are analyzed.Through the analysis of the mechanism,the modeling of single-phase intersection,two-phase single intersection and four-phase single intersection are studied.The established oversaturated intersection delay model can be used to assign the green time of each intersection by calculating the minimum delay to alleviate the oversaturation condition of the city road.Numerical simulation results verify the validity and availability of the modeling method.